2022
DOI: 10.1007/s10459-022-10134-6
|View full text |Cite
|
Sign up to set email alerts
|

Undergraduate paramedic students and interpersonal communication development: a scoping review

Abstract: The objective of this review is to examine the current literature related to interpersonal communication skill development within undergraduate paramedicine. Interpersonal communication is a vital paramedic skill, with evidence demonstrating it leads to improved patient outcomes and satisfaction and reduces medical errors. Interpersonal communication is a core capability set by paramedicine regulatory bodies, and it is the responsibility of accredited universities to ensure graduates are ready for industry and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Many studies have been conducted on enhancing the communication skills of EMTs, and their strategies have been examined. 59,60 In Japan, the strategic implementation of communication training in education for EMTs and in clinical settings may have had a negative association with burnout. 56 Moreover, there is evidence of a normalized perception that EMTs should have responsibility for transporting emergency patients as their training includes working in such emergency situations in pre-hospital settings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have been conducted on enhancing the communication skills of EMTs, and their strategies have been examined. 59,60 In Japan, the strategic implementation of communication training in education for EMTs and in clinical settings may have had a negative association with burnout. 56 Moreover, there is evidence of a normalized perception that EMTs should have responsibility for transporting emergency patients as their training includes working in such emergency situations in pre-hospital settings.…”
Section: Discussionmentioning
confidence: 99%
“…These are valuable sources of information to improve in-hospital care. Many studies have been conducted on enhancing the communication skills of EMTs, and their strategies have been examined [ 44 ]. In Japan, the strategic implementation of communication training in education for EMTs and in clinical settings may have had a negative association with burnout [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results are consistent with a previous finding that males were more likely to be active and independent in the development of interpersonal relationships ( Xia et al, 2014 ). Variable-centered studies focused on evaluating the level of interpersonal communication found that nursing students lacked interpersonal attributes and competence ( Mangan et al, 2022 ). Our person-centered study emphasized the shortage of independence and initiative in communicating with others and expanded our knowledge with respect to the tendencies and characteristics of interpersonal communication among FNSs.…”
Section: Discussionmentioning
confidence: 99%
“…The shortage of initiative and independence of ISS is adverse for their future academic and career development, as proactive communication is crucial to both the positive formation of PI and efficient nursing care ( Philippa et al, 2021 ). However, nursing interpersonal communication education has been undervalued in the past ( Mangan et al, 2022 ). Our study highlighted the necessity of increasing nursing students’ confidence in communicating with others.…”
Section: Discussionmentioning
confidence: 99%